19 марта, 04:01

Решите уравнение (6x+5) ^2-4x (3+9x) = 49

+2
Ответы (1)
  1. 19 марта, 04:18
    0
    Найдем х.

    (6 * x + 5) ² - 4 * x * (3 + 9 * x) = 49;

    (6 * x) ² + 2 * (6 * x) * 5 + 5² - 4 * 3 * x - 4 * 9 * x * x = 49;

    36 * x² + 10 * 6 * x + 25 - 12 * x - 36 * x² = 49;

    36 * x² + 60 * x + 25 - 12 * x - 36 * x² = 49;

    (36 * x² - 36 * x²) + (60 * x - 12 * x) + 25 = 49;

    x² * (36 - 36) + x * (60 - 12) + 25 = 49;

    x² * 0 + x * 48 + 25 = 49;

    48 * x + 25 = 49;

    48 * x = 49 - 25;

    48 * x = 24;

    x = 24/48;

    x = 1/2;

    x = 0.5.
Знаешь ответ на этот вопрос?